A Prospective Randomized Control Trial Comparing Vaginal Misoprostol Against Gemeprost As Cervical Priming Agent In Presurgical Evacuation Of Missed Abortion. - Md. Noor , Mansor (2001)
To compare the effectiveness, side effect and cost effectiveness of vaginal misoprostol against the standard drug, gemeprost, as cervical priming agent in pre-surgical evacuation in tirst and early second trimester missed abortion.